2018
DOI: 10.1155/2018/3927075
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Amana edulis Induces Liver Cancer Apoptosis

Abstract: HCC is one of the fastest-rising causes of cancer-related death. Novel therapeutic approaches for treatment are warranted. The goal of this study is to find effective components from Chinese herbal medicines, which is an important alternative source of anticancer medicine. To this end, six different herbs were selected from various traditional literatures. Soxhlet extractor was used to distill the strong polar and weak polar components of each herb. The inhibitive effect of each component was determined using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Adjuvant therapy, including chemotherapy, radiation and targeted therapy, are used for advanced PLC patients. In addition, accumulated studies showed that traditional Chinese medicine (TCM) is an alternative treatment for PLC because of its effective therapeutic outcome and fewer side effects compared to chemo-radiotherapy [ 5 , 6 ]. For example, Bei-Jia-Jian-Wan and Xiao-Chai-Hu-Tang are two of the most frequently used Chinese herbal medicine for PLC.…”
Section: Introductionmentioning
confidence: 99%
“…Adjuvant therapy, including chemotherapy, radiation and targeted therapy, are used for advanced PLC patients. In addition, accumulated studies showed that traditional Chinese medicine (TCM) is an alternative treatment for PLC because of its effective therapeutic outcome and fewer side effects compared to chemo-radiotherapy [ 5 , 6 ]. For example, Bei-Jia-Jian-Wan and Xiao-Chai-Hu-Tang are two of the most frequently used Chinese herbal medicine for PLC.…”
Section: Introductionmentioning
confidence: 99%
“…Different therapeutic strategies can be used for treatment of liver cancer including hormonal, biochemical, chemotherapeutic and molecular targeted therapies (Shaaban et al 2014). In addition, early and recent studies showed the promising participation of phytochemicals and herbal medicine in liver cancer therapy strategies (Abdel-Hamid et al 2018;Fan et al 2018;Li et al 2014;Li and Martin 2011). Formulation of phytochemicals in the form of nanoparticles enhances its therapeutic activity due to different factors and mechanisms which are fully discussed (Manivannan et al 2021;Beg et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tulipa edulis (Miq.) Baker belongs to the Liliaceae family and is a folk medicinal plant used to treat cancer diseases [ 1 , 2 ]. However, there have been few phytochemical and biological studies of this species reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few phytochemical and biological studies of this species reported to date. For example, 95% and 50% EtOH extracts could induce apoptosis in human gastric (SGC-7901) [ 1 ] and hepatoma (BEL7404, HepG2, and Huh7) [ 2 ] carcinoma cells, respectively. The polysaccharides prepared from A. edulis have anti-oxidant properties, including DPPH, OH − , and ABTS + scavenging activities [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%